Marketing Mix Analysis on Increasing Income of Floating Net Cage Farmers (Case Study in Kedisan Village, Kintamani) - Sudiarta; Agus Maha; I Putu Andre Suryadana (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
Batur's Lake is a crucial resource for both tourism and fisheries, notably for fish farming using floating net cages (FNC). FNC cultivation represents a rapidly growing industry, playing a pivotal role in the local economy. This study, conducted in Kedisan Traditional Village, Kintamani, Bangli Regency, employs analytical methods, including Partial Least Square (PLS) and descriptive analysis, to examine the impact of marketing mix elements on the income of FNC fish cultivators. With a sample size of 60 participants from the target population of floating net cage fish cultivators in 2023, key findings include: The marketing mix elements (product, price, promotion, and place) exhibit a positive and significant effect on the income level of FNC fish cultivators. Among these elements, the product emerges as the most influential indicator affecting the income levels of fish cultivators. Following enhancements in the quality of marketing mix elements, the average income level of FNC fish cultivators increases to Rp. 19,000,000 (Nineteen million rupiah) or 93.33% per harvest. These results underscore the importance of effective marketing mix strategies in elevating economic outcomes for fish cultivators engaged in FNC farming around Batur's Lake.